The Relationship Between Parenting Parents to Temper Tantrum in Pre-School Children - zakiyah, zakiyah; Nasution, Nurromsyah (Institute Of Computer Science (IOCS), 2024)
Temper tantrums are emotional outbursts such as screaming while rolling on the floor, kicking, banging your head against the floor or wall, hitting yourself or others, crying, cursing. The impact of temper tantrums on children can pose a risk of injury, if they occur in the environment of friends of the same age it can affect the development of children of their age, because the characteristics of children imitate what they observe. Parenting style is a factor in the occurrence of temper tantrums. This study aims to determine parenting patterns of temper tantrums in pre-school children. This type of analytic observational research with a cross sectional approach. This research was conducted at the Insan Madani Meukek Integrated Preschool in December 2022. The research sample is 76 respondents with total sampling technique. Data analysis using the chi square test with a significance level of a = 0.005 (95%). The results of the study found parenting styles with temper tantrums in pre-school children (p=0.000 <a 0.005). The results of this study are expected that parents can apply good parenting styles, such as democratic parenting because the risk of temper tantrums in children is lower than authoritarian and permissive parenting styles.